Cashless Behavior among Yogyakarta Muslim Students: Digital Financial Literacy and QRIS Payment Intention - Sokifah Dina; Utama Satria (SHS Web of Conferences)
The financial literacy index in Indonesia continues to increase, followed by an increase in the digital literacy index. The paper aims to investigate the effect of digital financial Literacy on QRIS payment intention among Yogyakarta Moslem students. The data were collected by using survey methods employing a purposive sampling approach. Structural equation modelling with the sample of 100 Yogyakarta Muslim student respondents was applied to test the influence of digital finance literacy on the intention to use QRIS payments. The results endorse that 1) Trust has a positive effect on the intention to use QRIS, 2) digital literacy has a positive effect on the intention to use QRIS, and 3) Knowledge, competency, and attitude do not have significant effects on the intention to use QRIS. This study suggests several theoretical and practical implications from the findings, as well as limitations and future directions.